Pengaruh Antusiasme Belajar dan Media Belajar Website “Sekolah Digital SMKN 3 Salatiga” Terhadap Prestasi Belajar Simulasi Digital - Yehoshua Yohan Ary Anando; Adriyanto Juliastomo Gundo (Peneliti.net, 2022)
Online learning is a solution to carry out learning during the COVID-19 pandemic. To support the implementation of online learning methods, learning enthusiasm and learning media on the